Juridical Analysis of Heirs Negligence of a Notary in Submission of a Notary Protocol who Dies - Mohamad Zanuar Soniaji; Siti Rodhiyah Dwi Istinah (Sultan Agung Notary Law Review, 2021)
The author in this paper takes the title above because he wants to know about the negligence of the Notary's heirs in the delivery of the Notary's protocol that has died, how is the responsibility of the heirs in the submission of the Notary's protocol that has died and is there legal protection for the community if the Notary protocol has not been submitted to another Notary or the recipient of the Notary protocol. This study uses a normative juridical approach and the data used are primary and secondary data obtained through interviews and literature study, data analysis is descriptive analytic. The responsibility of the heirs in the submission of the protocol of a notary who dies is to notify the notary's death to the Notary Supervisory Council (MPD) no later than 7 (seven) working days, and submit the protocol of the notary to another notary or the Regional Supervisory Council (MPD). The responsibility of the heirs is not related to the contents of the deed made by the notary, the responsibility for the deed of a notary who dies cannot be passed on to his heirs or to the notary who holds the notary protocol. Legal protection for the public if the Notary protocol has not been submitted to another Notary or the recipient of the Notary protocol, namely the Notary Protocol as a state archive if it is not immediately submitted to the competent authority, namely the Regional Supervisory Council or the Notary appointed as the Protocol Recipient exceeding the period determined by law, feared that it could be damaged, or even lost. Taking the Notary protocol that has not been handed over to the heirs is a form of legal protection to the community. The purpose of storing this Notary protocol is also a form of legal protection to the public. Notary protocol storage as a vital archive and must be stored and maintained properly as an anticipatory measure for conflicts by the parties in the future.